Community participatory approach: an important option in cardiovascular diseases prevention and control - Khalib Abdul Latiff (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2008)
Introduction : Despite the number of information generated by researchers, cardiovascular diseases problem has not clearly declined and perhaps in certain situation it is gradually increasing, affecting people who are previously at low risk. There is a tendency to believe that favourable outcomes can always be expected once intervention activities, like exercise promotion, are carried out, but practical experience gives rise to serious doubt. Methods : A greater understanding of the socialization mechanisms operating in the adoption of physical activity in CVD control and allow specific exercise prescriptions for community-based prevention and control is important. This paper highlighted the author’s feeling about controlling chronic diseases by mean of community intervention. Results : This analysis has strongly believed that the important impetus of any community intervention approach should be oriented in the form of “from people to people”. Conclusion : More emphasis needs to be placed on effective management and parameters for assessment of its management success.